A review of scuttle fly genera of Israel (Diptera: Phoridae), with new records and an identification key - Mostovski, Mike B. (Zootaxa, 2016)
A brief review of Israeli scuttle flies is given. The following genera are new records for the country: Arabiphora, Billotia, Chonocephalus, Menozziola, Phalacrotophora, Pseudacteon, Psyllomyia, and Puliciphora. Eighteen species—Arabiphora tenuifemorata, Chonocephalus depressus, Conicera floricola, Conicera similis, Gymnophora integralis, Gymnophora perpropinqua, Megaselia scalaris, Megaselia stigmatica, Menozziola schmitzi, Metopina formicomendicula, Phalacrotophora beuki, Phalacrotophora fasciata, Phora limpida, Phora tincta, Psyllomyia braunsi, Puliciphora rufipes, Spiniphora bergenstammi, and Tubicera lichtwardi—are added to the list of 56 phorid species previously known from Israel. Two species, Conicera similis and Megaselia scalaris, are recorded in association with the summer truffle Tuber aestivum commercially grown in northern Israel. The status of the Afrotropical Phora congolensis Beyer, 1965 is designated as nomen dubium. A lapsius calami, which led to an erroneous generic attribution of Metopina braueri in the paper on Israeli Metopina (Mostovski, 2016), is noted here. An identification key to the Israeli genera of scuttle flies, as well as notes on recognition and/or biology of individual species, are provided.